한국 전통의 도자 식기에서 느껴지는 대표 감성 - 박은정(Eun Jung Park) (스마트미디어저널, 2022)
It is necessary to discover Korea's diverse traditional culture and publicize it to the world to continue the Korean Wave and develop it in a more positive direction. The present study proposes methods for publicizing little-known 'traditional Korean ceramic tableware' by focusing on Hansik, which is the most frequently published in the British Oxford Dictionary among Korean traditional cultures and can best represent Korean food. To this end, the present study measured cultural recipients' emotions regarding traditional Korean ceramic tableware to derive the 'representative emotions felt regarding traditional Korean ceramic tableware' as a method to reflect it in the design. First, the Delphi Technique was carried out based on 182 emotional vocabulary items collected from existing studies to create 33 groups of emotional vocabularies with similar concepts. In addition, among the emotional vocabularies included in each of the 33 groups, those of overlapping concepts were regrouped based on the characteristics of traditional Korean ceramic tableware, and the most appropriate emotional vocabularies were extracted and reduced to 75. A survey was carried out with 135 cultural recipients experienced with traditional Korean ceramic tableware to derive 32 representative emotions felt regarding traditional Korean ceramic tableware. Finally, from the results of a factor analysis of 32 representative emotions, this study classified vocabulary into six emotion categories including 'aesthetic, pleasure, freshness, ownership, satisfaction, and comfort'. The six emotion categories and 32 representative emotions derived from this study's results can be utilized to measure emotional levels felt by cultural recipients while using traditional Korean ceramic tableware. 한류의 열풍을 지속하고 보다 긍정적인 방향으로 발전시키기 위해서는 한국의 다양한 전통문화를 발굴하여 세계인에게 널리 알릴 필요가 있다. 이에 본 연구에서는 한국 전통문화 중에서 영국 옥스퍼드 영어 사전에 가장 많이 추가로 실린 한식에 착안하여 한식을 가장 돋보이게 담아낼 수 있으나, 미쳐 알려지지 않은 '한국 전통의 도자 식기'를 널리 알릴 방안을 제안하고자 한다. 이를 위해 한국 전통의 도자 식기에서 문화수용자의 감성을 측정하여 디자인에 반영할 방안으로 '한국 전통의 도자 식기에서 느껴지는 대표 감성'을 도출하였다. 우선 기존 연구에서 수집된 감성 어휘 182개를 기반으로 델파이 기법을 실시하여 유사한 개념의 감성 어휘를 33개로 그룹화하였다. 또한 33개의 그룹마다 포함된 감성 어휘 중에서 한국 전통의 도자 식기의 특성을 중심으로 중복되는 개념의 감성 어휘들을 다시 그룹화하고 가장 적합한 감성어휘를 추출하여 최종 75개로 축약하였다. 또한 한국 전통의 도자 식기를 체험한 경험이 있는 문화수용자 135명을 대상으로 설문조사를 진행하여 한국 전통의 도자 식기에서 느껴지는 대표 감성 32개를 도출하였다. 마지막으로 요인분석을 통해 32개의 대표 감성을 분석한 결과 '심미감, 유쾌감, 신선감, 소유감, 만족감, 안락감' 등 6개의 감성 카테고리로 분류하였다. 본 연구의 결과로 도출한 6개의 감성 카테고리와 32개의 대표 감성은 한국 전통의 도자 식기를 사용하면서 문화수용자들이 느껴지는 감성 정도를 측정하는 데 효과적으로 활용할 수 있을 것으로 기대한다.